Recontextualizing Politics of Noun Phrases in the New York Times Editorial - Kushmi, Angel (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
This research paper is an effort to recontextualize the politics of noun phrases on the New York Times editorial published on January 7th, 2016 entitled “North Korea Flexes Its Nuclear Muscle”. It examines how the recontextualization of these noun phrases can contribute to shaping public discourse about political events and ideas. Through a critical discourse analysis, Norman Fairclough’s concept of recontextualization and Theo Van Leeuwan’s discourse and function of language, the study demonstrates how the editorial uses noun phrases to mobilize support for certain political views while demonizing the opposing ones. To recontextualize the politics of noun phrases, deem how different political ideologies and movements may use specific language to reinforce their beliefs and goals. By recontextualizing the noun phrases, the editorial produces a particular political agenda that is likely to influence the reader’s opinions and attitudes towards certain political issues. The findings suggests that the language used in political discourse is a powerful tool that can be used to shape public opinion and that the manipulation of language should be a subject of public concern and also that the ideology can be changed by playing through choice of certain noun phrases.